Rapid karyotypic evolution with high diploid number variation in a rare genus of bromeligenous frogs - Pedroso, Ricardo Neves; Santos, Marcus Thadeu Teixeira [UNESP]; Lourenço, Luciana Bolsoni (Canadian Science Publishing, 2022)
Bromeligenous Crossodactylodes is a leptodactylid genus closely related to Paratelmatobius and Scythrophrys. The diploid number in all karyotyped species of these two latter genera is 24, which diverges from the modal diploid number (2n = 22) in the family. Here, we analyzed three species of Crossodactylodes and found karyotypes with 2n = 30, 2n = 32, and 2n = 36, diploid numbers that have not been reported in any other diploid leptodactylid species to date. Reconstruction of the ancestral chromosome number indicated that the diploid number changed from 22 to 24 in the common ancestor of Crossodactylodes, Paratelmatobius, and Scythrophrys, and that progressive increases in diploid number have occurred in Crossodactylodes. The large number of telocentric/subtelocentric chromosomes in karyotypes with higher diploid numbers raises the possibility that centric fissions may have occurred during the evolution of Paratelmatobiinae. Three metacentric chromosomes, probably involved in fission events, were inferred to be present in the common ancestor of all species of Crossodactylodes, but in C. bokermanni. Chromosome mapping of the satellite DNA PcP190 suggests homology between one arm of metacentric chromosome 1 of Crossodactylodes sp. 3 and telocentric chromosome 2 of C. itambe, supporting one of the presumed centric fission events.
Keywords: Chromosome evolution; Anura; Centric fission; Crossodactylodes; Paratelmatobiinae; Cromossomos; Anuro